Market Size, Sunk Costs of Entry, and Transport Costs An Empirical Evaluation of the Impact of Demand-Side Factors versus Supply-Side Factors on Manufacturing Productivity - Jones, Patricia H. (The World Bank, 2019)
This paper uses plant-level, panel data from the Ethiopian manufacturing census to estimate the effects of demand-side and supply-side factors on industrywide aggregate productivity. The paper focuses on the effects of three factors: (1) local market size, (2) the value of transportation costs that firms incur in selling to customers outside their market, and (3) licensing fees needed to enter the market. Identification is based on a model of production under monopolistic competition, which enables interpreting the estimated coefficients of a reduced form, dynamic productivity equation. The paper analyzes 11 industries in Ethiopia over 2000 to 2010. Several interesting results emerge. In the most parsimonious specification, the estimated coefficients are consistent with all three predictions of the model-but only for one industry: cinder blocks. In this industry, the expansion of the local market boosts industrywide total factor revenue productivity, while increases in transport costs and licensing fees reduce it. The picture is somewhat mixed in the other 10 industries but broadly consistent with the predictions of the model